Financial Performance of Islamic Banking: Overview of the Intellectual Capital of Bank Syariah Indonesia - Suhendi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This think about points to analyze the impact of mental capital (IC) on budgetary execution at Indonesian Sharia Banks. The theory in this ponder was tried utilizing the variant-based Auxiliary Condition Modeling (SEM) strategy or Fractional Slightest Square (PLS) including a few factors from mental capital (IC) altered for Islamic managing an account to be specific iB-VACA, iB-VAHU, iB- STVA. The comes about of the think about appear that iB-VAIC and iBVACA have an impact on money related execution. Though iB-VAHU has no impact on budgetary execution, and iBSTVA contains a negative impact on budgetary execution.